KEPADATAN POPULASI Helicoperva armigera (Hubner) (Lepidoptera: Noctuidae) PADA TANAMAN TOMAT DI KAMPUNG BATU KECAMATAN DANAU KEMBAR KABUPATEN SOLOK - Suherlinda, Suherlinda; Jasmi, Jasmi; safitri, Elza (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ Population of fruit caterpillar (Helicoperva armigera) on tomato plants can reduce yield. In the area of Kampung Batu Danau Kembar District of Solok is the most widely caterpillars cause damage to tomato plants. Based on the data obtained from the UPTD Kampung Batu District of Solok, in 2013 stated that in 2011 the production of tomatoes in the amount of 85.46 tons and declined in 2012 to 69.16 tons. In connection with the matter, has done research on population density Helicoperva armigera (Lepidoptera:Noctuidae) on tomato plants in Kampung Batu Danau Kembar District of Solok which aims to determine the population density Helicoperva armigera on tomato plants in Kampung Batu Danau Kembar District of Solok.The study started from August to September 2013 with a descriptive survey method is by way of direct collection of the Helicoperva armigera larvae at the site of research. Field sampling was conducted on tomato plants age of 3 months and 4 months after planting. Physical environmental factors measured are temperature and humidity. Widely used as a study area of about 30 x 20 m. From the research that has been conducted in Kampung Batu Danau Kembar District of Solok acquired traits Helicoperva armigera found on tomato plants in Kampung Batu Danau Kembar District of Solok are long of caterpillar that is found at the age of 3 months and 4 months ranged from 1.5 cm to 3 cm, color of caterpillars were found ranging from yellow-green to brown. The highest population density of fruit caterpillar on tomato plants aged 3 months after planting is 5.40 individual/stem, while the lowest population density of fruit caterpillars on tomato plants aged 4 months after planting is 2.70 individual/stem.